Pitching Perspectives on Disability: Voyage Experiences of Disabled Sailors on Tall Ships - Catherine Lamont-Robinson; Val Williams; Trevor Thompson (Scandinavian Journal of Disability Research, 2018)
This paper explores the experiences of disabled sailors on board a tall sailing ship, adapted for accessibility. Eight disabled sailors kept audio diaries and created artwork during the voyages, as well as taking part in interviews afterwards. In reporting their accounts, we explored what it meant for participants to go to sea. We became particularly interested in embodied activities on board ship, the ways in which sailing created and highlighted new identities, and the social aspects of sailing in a team. Our account brings together some of the central concerns in Disability Studies with the perspectives of social practice theorists, and seeks to add layers of meaning to both approaches. Since this is a nautical project, the paper is structured by following the stages of going to sea, and in the words of one participant, we seek to ‘join the dots between medical, academic and anecdotal knowledge’.